Urban Air Quality Guidance Based on Measures Categorization in Road Transport - Beti Angelevska; Vaska Atanasova; Igor Andreevski (Civil Engineering Journal, 2021)
Air pollution is a cause for serious concerns in urban areas in Republic of North Macedonia. Intensive development of road transport increases the main air pollutants’ concentrations - particulate matter and nitrogen dioxide, whose monitored values are continuously exceeding the limit. The main disadvantage of the national plans and annual reports is the absence of comprehensive and categorized list of reduction/mitigation measures for road transport impacts on air quality. Analyzing the current air pollution problem and road transport contribution this paper provides the needed and detailed categorization of short-to-long term reduction/mitigation measures consisting of five subcategories. Based on measure categorization, a guiding frame for urban air quality is designed, intended for further support and assistance for local authorities in the process of air pollution control. Designed with integrated activities, the air quality guidance enables them to select suitable measures to manage road transport pollution and to evaluate their effects estimating the changes in air pollution levels. Hence, the guidance can be used for thorough planning of air quality issues caused by road transport and for policy making. Contributing for urban air quality improvement the guidance is a first step towards the implementation of air pollution management in urban areas. Doi: 10.28991/cej-2021-03091651 Full Text: PDF